Fractal Statistical Study on the Strength of Jointed Rock Mass. (4th May 2022) - Li, Fangtao; Hu, Zhiping; Ren, Xiang; Ma, Jiakuan; An, Xuexu; Zheng, Yunxin; Zhang, Yonghui
Abstract : The failure probability and strength of jointed and fractured rock mass under water pressure action place important constraints on the safety and stability of rock mass engineering. In this study, two strength calculation models for rock mass joint rupture failure and shear slip failure are established according to different relative sizes and working conditions, and the effects of fractal dimension, water pressure, and number of cracks on the strength and failure probability of rock mass are analyzed. The most unfavorable dip angle under shear-slip conditions is calculated. The proposed models accurately reflect the failure probability and strength of jointed rock mass, and different strength calculation methods should be selected according to the specific working conditions. The effect of water pressure on the strength of jointed rock mass is sensitive to the failure mode. Reasonable drainage should be carried out according to the different failure modes when constructing tunnels with abundant groundwater, and certain drainage or water plugging construction schemes are not necessarily applicable to all cases. The dip angle at which joint fissures are most prone to shear slip is given as π /4 + φ /2, where φ is the jointed rock mass strength parameter. An increase in the fractal dimensions, external stress, and number of fractures will enhance the rock mass failure probability regardless of failure mode. Controlled blasting and advanced grouting reinforcement measures are recommended when a tunnel traverses through a joint fissure zone to reduce the number of cracks generated in the surrounding rock and thus improve its strength and stability.